Iklan Luar Ruang di Yogyakarta Pasca Pandemi Covid-19 dalam Kajian Sosio Desain - Prayanto Widyo Harsanto; Anak Agung Gede Bagus Udayana (Mudra Jurnal Seni Budaya, 2023)
This study aims to identify and critically analyze Outdoor Advertising in Yogyakarta using a socio-design approach. Outdoor Advertising, such as banners, banners, posters, billboards, and other media installed in every corner of Yogyakarta, is a dilemma. According to the view of a person or institution/industry, existence of Outdoor Advertising is an effective medium for conveying promotional messages to the public. Meanwhile, for regulators, especially for local governments, this can provide regional income through relatively high taxes. Nevertheless, on the other hand, the rise of Outdoor Advertising raises aesthetic, security, and environmental management issues in Yogyakarta City. This study uses a qualitative method with a socio-design approach (social aesthetics). The social-aesthetic process appreciates design work in a socio-environmental context, both the human environment, the natural environment, and the social environment. The design work in this study is the design of Outdoor Advertising is an essential variable because the delivery of messages through Outdoor Advertising will determine the content, shape, and type, as well as the location or installation. When viewed from a functional context, advertising is to help market products and services persuasively. From the aesthetic context, outdoor advertising displays must focus on Yogyakarta's social, economic, cultural, and environmental aspects. The results of this study indicate that Outdoor Advertising is needed for communicators to convey messages on products/services. As an essential regulator, the local government makes public spatial planning policies related to ad placement. Therefore, Outdoor Advertising can help increase the positive perception of the correlated people to form the image of the Yogyakarta city planning, which is unique and has a comfortable heart.